Human rights and social justice : social action and service for the helping and health professions social action and service for the helping and health professions - Wronka, Joseph, 1948- (Los Angeles : Sage Publications, 2008)
[Publisher-supplied data] Human Rights and Social Justice: Social Action and Service for the Helping and Health Professions has a unique perspective that views human rights as the bedrock of social justice. It provides a clear blueprint how human rights and social justice concerns can serve as a conceptual framework for policy and practice interventions among the helping and health professions. Key Features and Benefits Provides both historical and philosophical perspectives on human rights principles, with the Universal Declaration of Human Rights as the centerpiece Succinctly summarizes for the educated layperson core principles of other major human rights documents, such as international conventions on: Civil and Political Rights (ICCPR); Economic, Social, and Cultural Rights (CESCR); the Elimination of Discrimination Against Women (CEDAW); the Eradication of Racial Discrimination (CERD); the Rights of the Child (CRC); Torture (CAT); the Rights of Indigenous Peoples; Medical Ethics; and the Protection of Persons with Mental Illness Viewing social justice as struggle, advocates a multi-pronged approach dealing with whole, at-risk, and clinical populations to promote physical and mental well-being and eradicate social and individual pathology Examines social actions like human rights education, resolutions, and bills; the arts and the media; humanistic administration; grant writing; social entrepreneurship; clinical interventions; and quantitative and qualitative research that fcan promote human dignity, public health, human development, and the creation of a human rights culture, which is a "lived awareness" of human rights principles in mind, heart, and body "Human rights and social justice is an important contribution to social justice theory and practice. Dr. Wronka presents a solid and sound argument that human rights, as proclaimed in 1948 by the United Nations in the Universal Declaration of Human Rights ought to serve as the foundation for socially just ways of life.David G. Gil Professor, Heller School for Social Policy and Management, Brandeis University "Brilliantly demonstrates that human rights provides a powerful framework for the helping and health professions. Blending in-depth knowledge of human rights with theory and practice in the helping professions, Wronka presents a comprehensive model to guide actions from global to micro levels, and from professional to personal. Lynne M. Healy Center for International Social Work Studies "At once accessible and learned, theoretical and practical. Wronkas groundbreaking text, reflecting comprehensive knowledge melded with a commitment to social action, is worthy of every professionals library. It should be required reading in schools. Janice Wood Wetzel International Association of Schools of Social Work Intended Audience This text is an excellent core or supplement test for social policy and practice courses encompassing social work, psychology, psychiatry, public health, medicine, nursing, ethics, law, theology, philosophy, the arts, peace studies, political science, and world citizenship. Scholars, activists, and practitioners will find it a valuable reference for years to come. Library of Congress subject headings for this publication: Human services. Human rights. Social justice.
pt. 1. Human rights as the bedrock of social justice. Introduction -- Before and beyond the universal declaration of human rights -- pt. 2. Building from the foundation. An advanced generalist/public health model and whole population approaches to human rights and social justice -- At-risk and clinical social action and service strategies toward the creation of a human rights culture -- A human rights/social justice approach to research-action projects for the helping and health professions -- Ground rules.
Includes bibliographical references (p. 297-307) and index.
Keywords: Human services; Human rights; Social justice; Ethics, Medical; Human Rights; Social Justice; Social Work -- Ethics